Unilateral minimal ovarian cancer with peritoneal implant and an intraepithelial carcinoma in the contralateral fallopian tube - Terada, Hiroyuki; Honda, Ken-ichi; Nakagawa, Tomoko; Takase, Aki; Kurihara, Yasushi; Ando, Tetsuji; Tendo, Masashige; Hori, Takeshi; Miyamoto, Keiko; Inaba, Mayumi; Ohsaw, Masahiko (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Here we present postoperative pathology of an 82-year-old woman who presented with massive ascites, and an implant-like adenocarcinoma on her intrapelvic peritoneum, which revealed a minimal (<5mm) serous adenocarcinoma on her left ovary and an intraepithelial carcinoma on inner surface of her right Fallopian tube. The left ovarian serous adenocarcinoma may have originated as an intraepithelial carcinoma on contralateral Fallopian tube.